Restorative Justice for Perpetrators of Theft Crimes Caused by Poverty - Saputra, David Nugraha; Atu Karomah; Putri, Febi Eka (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2024)
This research aimed to explore how the concept of Restorative Justice is applied in resolving criminal acts of theft caused by poverty. Due to the many weaknesses and problems that arise as a result of positive repressive law enforcement, it is deemed necessary to resolve minor criminal cases through non-penal measures by fulfilling the principles of Restorative Justice to safeguard people's lives and to fulfill a sense of justice, rather than carrying out and resolving criminal cases. through the courts, especially for perpetrators of criminal acts of theft caused by poverty. The research method used is Normative Juridical. The research employed a Normative Juridical approach to analyze the concept of Restorative Justice in addressing theft crimes related to poverty. From the research results, it was found that criminal acts of theft which are usually committed because of poverty can be carried out with Restorative Justice efforts considering that the criminal threat under Article 362 of the Criminal Code is no more. from five years because this is one of the requirements according to Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice and Republic of Indonesia Regulation Number 6 of 2019 concerning Criminal Investigation.